Factors Contributed to a Difficult-To-Treat Juvenile IdiopathicArthritis: A Systematic Review and Meta Analysis - Louis Edwin Wirya (Indonesian Rheumatology Associantion, 2024)
Background: Juvenile Idiopathic Arthritis is the foremost commonunremitting rheumatic illness in childhood, with a global prevalence rangingfrom 16 to 150 per 100.000 population. However, in some cases, clinicianmay face a difficult-to-treat Juvenile Idiopathic Arthritis (D-JIA), whichindicate to a group of patients who have not affected by administration ofstandard anti-rheumatic drugs. This study aims to identify factors thatcorrelate to D-JIA. Methods: We conducted a systematic review and metaanalysis, collecting studies from PubMed, Scopus, Embase, Cochrane, andGoogle Scholar. Eligible Studies were trials that analyze factors that maycontribute to D-JIA. Results: Six studies were included, enrolling 1.177patients. Female composes 70.9% (835) of the population (OR 1.04, CI 95%0.83-1.31, p=0.72). Median of age and duration of disease respectively were5.79 years and 11.06 months. Some factors correlate with occurancy of DJIA including Caucasian race (OR 0.96, CI 95% 0.44-2.07, p=0.91), ANAnegative (OR 1.77, CI 95% 1.42-2.22, p<0.00001), HLA B27 positive (OR1.86, CI 95% 0.85-4.08, p=0.12), prescence of atypical skin lesion (OR 8.5,CI 95% 1.6-72.4, p=0.022), and spesific subtype of JIA such as Oligoarthritis(OR 0.86, CI 95% 0.70-1.07, p=0.17), Poliarthritis (OR 1.77, CI 95% 1.422.22, p<0.00001), Systemic-type (OR1.22, CI 95% 0.60-2.49, p=0.58),Psoriatic (OR1.61, CI 95% 0.69-3.78, p=0.27), Enteritis-related (OR 1.33, CI95% 0.68-2.59, p=0.40), and Undiffrentiated (OR 1.46, CI 95% 0.55-3.83,p=0.45). Conclusion: Eventhough many factors identified, but only ANAnegativity, presence of atypical skin lesion, and Poliarthritis subtype thathave been statistically proved related in the development of D-JIA. Thisfinding may be due to the study's limitations and remaining differences insubsequent results. Future studies are needed for further analysis regardingthis issue.